Altered cardiovascular health in COVID-19 patients - Tapas Pramanik, (Journal of Physiological Society of Nepal, 2022)
Mortality due to cardiac cause is common amongst COVID-19 patients. Myocarditis, decompensated heart failure, acute coronary syndrome, sinus tachycardia, atrial fibrillation and right bundle branch block (RBBB) were noted2 in many hospitalized COVID patients. Studies conducted time to time, in various countries and hospitals registered various numbers and percentages (%) of patients suffering from myocardial injury ranging from 8% to70% among the COVID victims. Infection by COVID-19 causes fever and inflammation in many organs and may cause serious myocarditis, even in those with no previous clinical history of cardiovascular disease.4 This infection may cause cardiomyopathy, altered rhythm, and reduction in optimum cardiac output.